The Internalization of Responsibility Values Through Worship Habituation to Enhance Students’ Religious Awareness - Juhansyah Juhansyah; Suyadi Suyadi; Hendro Widodo (Early Publishing, 2025)
This study aims to describe the process of internalizing the value of responsibility through a worship habituation program in increasing the religious awareness of elementary school students. This research employs a qualitative approach with a case study design conducted at SDIT Luqman Al Hakim 2 Yogyakarta. The research subjects consisted of the principal, vice principal for curriculum, Islamic Religious Education teachers, homeroom teachers, and students. Data were collected through participatory observation, in-depth interviews, and documentation of school activities related to the implementation of worship habituation. The data were analyzed using the stages of data reduction, data display, and conclusion drawing. The findings reveal that the internalization of the value of responsibility occurs through three stages: value transformation, value transaction, and value transinternalization. These stages are implemented through various structured and continuous worship habituation activities, including dhuha prayer, congregational prayer, dhikr, Qur’an recitation, and morning assemblies. Through these activities, students gain cognitive understanding of responsibility in worship and gradually develop affective awareness and behavioral practice in daily life. The study indicates that worship habituation serves as an effective medium for internalizing responsibility values and strengthening students’ religious awareness, contributing to the development of character education based on religious values in elementary schools.